2008
DOI: 10.1097/yic.0b013e3282f94ad0
|View full text |Cite
|
Sign up to set email alerts
|

The Nisonger Child Behavior Rating Form: typical IQ version

Abstract: The Nisonger Child Behavior Rating Form (NCBRF) has been used in several large studies of risperidone in children with low IQs (36-84) and disruptive behavior disorders (conduct disorder and oppositional defiant disorder). We wanted to develop a companion instrument for assessing 'typically developing' children and adolescents. In this study, we modified the NCBRF and obtained parent ratings on 485 typically developing children attending regular classes. We also obtained parent ratings on 46 children with cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 14 publications
0
29
0
Order By: Relevance
“…D-Total scores >12 are considered high (mean -SD in the normative sample, n = 471, was 10.09 -11.44); a score > 27 (90th percentile) was required for study entry. The mean normative score on the ADHD Total subscale was 6.82 -7.06 (n = 479), and the mean normative score for the Positive Social subscale was 19.96 -6.28 (n = 485) (Aman et al 2008).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…D-Total scores >12 are considered high (mean -SD in the normative sample, n = 471, was 10.09 -11.44); a score > 27 (90th percentile) was required for study entry. The mean normative score on the ADHD Total subscale was 6.82 -7.06 (n = 479), and the mean normative score for the Positive Social subscale was 19.96 -6.28 (n = 485) (Aman et al 2008).…”
Section: Methodsmentioning
confidence: 99%
“…The primary outcome measure in the study was the NCBRF Typical IQ version (Aman et al 2008) Disruptive Total Score (D-Total). The NCBRF is a parent-report measure with excellent psychometric properties and demonstrated sensitivity to drug effects.…”
Section: Methodsmentioning
confidence: 99%
“…The initial publication describing results for the primary hypotheses 16 reported that Augmented treatment was superior to Basic treatment in reducing the severity of disruptive behaviors (Cohen's d =.43) as measured by the primary outcome measure, the parent-completed Nisonger Child Behavior Rating Form Disruptive total (NCBRF D-total). 17 Moreover, there was little evidence of increased risk of adverse events (AEs) at the end of the acute treatment phase for children receiving Augmented treatment. The present article expands on our previous report by addressing several new topics including (a) drug effects for DSM-IV -defined ADHD, ODD and CD symptoms and (b) interpersonal peer aggression; (c) caregiver reports of symptom-induced impairment; (d) teachers' ratings of treatment effects to include school functioning; and (e) informant discrepancy (i.e., differences in parents' versus teachers' ratings of drug response).…”
Section: Introductionmentioning
confidence: 99%
“…Measures relevant to the reanalysis include the Disruptive Total (D-Total) of the Nisonger Child Behavior Rating Form –Typical IQ (NCBRF) 10 and the severity and improvement ratings from the Clinical Global Impressions scale (CGI-S and CGI-I). 11 The NCBRF D-Total score is a combination of the Conduct Problem and Oppositional Behavior subscales.…”
Section: Methodsmentioning
confidence: 99%